Performance Evaluation of CLM5 in Simulating Evapotranspiration over Pearl River Basin - WANG Dayang (Renmin Zhujiang)
To investigate the simulation performance of the Community Land Model version 5 (CLM5) in simulating terrestrial evapotranspiration,this paper simulated the surface processes in the Pearl River Basin (PRB) from 1989 to 2018 with CLM5.For validation,the remote sensing-based GLEAM ET products were used as reference for the evaluation of the model's simulation performance.The evaluation was based on temporal variability analysis and spatial pattern analysis.The results show that CLM5 underestimates the evapotranspiration in the PRB to varying degrees,with the relative error of average annual evapotranspiration being -16.07% in the basin.The underestimation is mainly attributed to the underestimation of low evapotranspiration in the cold season. By contrast,CLM5 performs better in the simulation of high evapotranspiration in the warm season.Spatially,CLM5 has good performance in the southeast,south,and west of PRB,while poor performance in the northern PRB.This study can provide a guideline for the development of the evapotranspiration module in CLM5.